Evaluasi desain sudu turbin gas model S-20 tipe aksial menggunakan CFD - Fatkur Rachmanu (Universitas Muhammadiyah Metro, 2020)
In the design of a gas turbine as a power plant, the turbine manufacturer always makes a redesign for improvement from the previous design (continuous improvement). This study discusses the redesign of a gas turbine for S-20 model power plant. The use of software that has been used to get more tangible from the basic theory of a gas turbine blade in this case is the average speed triangle. Can be seen a change in the flow of gas that enters the rotor and stator to be absorbed by the kinetic energy of the gas that hit the blade to produce a larger number of shaft paths. The results of this design produce for enthalpy in high pressure turbine is 1,211,129 J/kg, with mechanical power is 2,747 Watt. Produce view of shape is ellipse on leading edge and trailing edge and choice of twist turbine blade stating from hub, meridian and tip. In this research flow of gas depend on rotor turbine blade position and rotating speed of rotor. Besides that velocity of gas, gas mass, high of stator and rotor blade.Keywords: Blade, turbine, gas, Saturn, Computational Fluid Dynamic (CFD).